2015
DOI: 10.1093/ejcts/ezv072
|View full text |Cite
|
Sign up to set email alerts
|

Results of extracardiac conduit total cavopulmonary connection in 500 patients

Abstract: The early to mid-term outcomes of post-EC-TCPC patients managed with individualized pharmacotherapy were excellent, with low mortality and morbidity rates; however, development of late-occurring morbidities specific to Fontan physiology, including exercise intolerance and liver disease, must be carefully monitored during the long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 26 publications
1
49
0
2
Order By: Relevance
“…CHARM study indicated PAP C 17 mmHg as one of the ''important hemodynamic variables associated with adverse outcomes'' in catheterization of single ventricle [16]. This cutoff point is more compatible with our situation in a developing country, although it is higher than the cutoff point of 10 mmHg which has been reported by Nakano et al [14]. It is worthy to note that the equations, concept of correlations between IVC-CI and mean PAP and the clinical usage of these indexes for quantitative long-term follow-up of an individual patient are not significantly dependent on this cutoff point.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…CHARM study indicated PAP C 17 mmHg as one of the ''important hemodynamic variables associated with adverse outcomes'' in catheterization of single ventricle [16]. This cutoff point is more compatible with our situation in a developing country, although it is higher than the cutoff point of 10 mmHg which has been reported by Nakano et al [14]. It is worthy to note that the equations, concept of correlations between IVC-CI and mean PAP and the clinical usage of these indexes for quantitative long-term follow-up of an individual patient are not significantly dependent on this cutoff point.…”
Section: Discussionsupporting
confidence: 86%
“…However, lack of definite and accurate noninvasive methods for quantitative estimation of PAP, collateral evaluation and difficulty in obtaining good quality echocardiographic images in adults with congenital heart disease is challenging areas in TCPC patients. Cardiac catheterization is the gold standard method for assessment of TCPC pathway, PAP assessment and sometimes intervention as the next step [14]. Some experts routinely perform angiography in TCPC patients, but controversy over the need of angiography in TCPC patients persists due to the invasive nature of the procedure, ionizing radiation and risk of complications, such as emboli [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerando os avanços, tanto em decorrência de melhorias na técnica cirúrgica, como no manejo peri-operatório, a sobrevida desta população é bastante satisfatória, ao redor de 85% de sobrevida em vinte anos, nos melhores centros do mundiais (9,(18)(19)(20).…”
Section: Agradecimentosunclassified